Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, Kecerdasan Spiritual dan Locus of Control terhadap Perilaku Etis Auditor (Studi Pada Kantor Akuntan Publik di Kota Malang) - Hastuti, Ambar Woro; Putri, Riska Dwiannur (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze and provide evidence regarding the influence of Emotional Intelligence, Intellectual Intelligence, Spiritual Intelligence, and Locus of Control on the Ethical Behavior of Auditors. The population in this study consists of auditors working at Public Accounting Firms in Malang City. The total number of auditors in this study is 65 respondents. The sampling technique used in this research is purposive sampling. The data collection method employed is a questionnaire, distributed directly in physical form. This research utilizes Multiple Linear Regression Analysis, and to determine the hypothesis, F,t, and R2 are conducted using SPSS Version 26. The results of the hypothesis testing indicate that emotional intelligence and spiritual intelligence significantly affect the ethical behavior of auditors, while intellectual intelligence and locus of control do not have a significant impact on the ethical behavior of auditors.